Performance factors managment desision-making IN AGRICULTURAL ORGANIZATIONS (Путеводитель предпринимателя)
This article highlights the main factors that influenceing at improvingmanagerial decision making in agricultural organizations. The quantitative effect offactors with the help of correlation-regression model and analyzed the application ofmodel-specific holdings of the Smolensk region.